2020
DOI: 10.21203/rs.3.rs-18846/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triglyceride Glucose Index for the Detection of Asymptomatic Coronary Artery Stenosis in Patients With Type 2 Diabetes

Abstract: Background: Triglyceride Glucose (TyG) index has been associated with an increased risk in cardiovascular events. Silent coronary disease is common in patients with type 2 diabetes. In Vietnam, a low-middle income country, the burden of cardiovascular disease is growing simultaneously with the epidemiologic transition. Our aim was to assess the prevalence of coronary stenoses (CS) in patients with type 2 diabetes and no history or symptom of cardiovascular disease and to investigate the association between TyG… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…27,29,32,34,36,37 In Rongjiong Zheng, Yushan Mao studied the TyG index of 4686 people for 9 years, showing the significance of TyG in predicting hypertension in the Chinese population. 34 Other centers in the Asian region also examined the TyG index in clinical practice although in a small number of patients, 38,41 and also examined the role of TyG index in the patients with hypertension. 29,37,39 All studies show the value of the TyG index when compared to the HOMA-IR index in assessing IR.…”
Section: Why Tyg Indices Can Be Selected For Screening For Insulin mentioning
confidence: 99%
“…27,29,32,34,36,37 In Rongjiong Zheng, Yushan Mao studied the TyG index of 4686 people for 9 years, showing the significance of TyG in predicting hypertension in the Chinese population. 34 Other centers in the Asian region also examined the TyG index in clinical practice although in a small number of patients, 38,41 and also examined the role of TyG index in the patients with hypertension. 29,37,39 All studies show the value of the TyG index when compared to the HOMA-IR index in assessing IR.…”
Section: Why Tyg Indices Can Be Selected For Screening For Insulin mentioning
confidence: 99%
“…Other cardiovascular disease surrogate measures related to the TyG index include coronary artery calcium score [20], IMT of carotid arteries, and arterial stiffness [21,22]. A few studies have found a link between the TyG index and cardiovascular disease in high-risk patients with diabetes and chronic renal disease [23][24][25]. To our knowledge, our study is the rst to show an independent relationship between the TyG index and the thoracic aorta IMT.…”
Section: Discussionmentioning
confidence: 62%
“…18 The TyG index was reported to be related to a higher risk of cardiovascular diseases and mortality. 19 In addition, some studies showed that the TyG index was significantly associated with the severity of coronary artery stenosis, 20 arterial stiffness, 21 and vascular calcification. 22 A study found that the TyG index was an independent predictor of PAD complexity based on a small sample size of 71 PAD patients.…”
Section: Discussionmentioning
confidence: 99%